RHIVDB: A Freely Accessible Database of HIV Amino Acid Sequences and Clinical Data of Infected Patients - Tarasova, Olga; Rudik, Anastasia; Kireev, Dmitry; Poroikov, Vladimir (Frontiers in Genetics, 2021)
HIV infection remains one of the most severe problems for humanity, particularly due to the development of HIV resistance. To evaluate an association between viral sequence data and drug combinations and to estimate an effect of a particular drug combination on the treatment results, collection of the most representative drug combinations used to cure HIV and the biological data on amino acid sequences of HIV proteins is essential. We have created a new, freely available web database containing 1651 amino acid sequences of HIV structural proteins (reverse transcriptase, protease, integrase and envelope protein), treatment history information, and CD4 cell count and viral load data available by the user’s query. Additionally, the biological data on new HIV sequences and treatment data can be stored in the database by any user followed by an expert’s verification. The database is available on the web at http://www.way2drug.com/hivdb.